2018
DOI: 10.5713/ajas.18.0174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotype by environment interactions on milk production traits of Holstein cows in Southern Brazil

Abstract: A slight change in genotype between areas was expected since no significant genotype by environment interactions were identified, facilitating the process of selecting Holstein cattle in southern Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…Relevant FY (277.81 kg/lactation/year) and PY (255.47 kg/lactation/year) were observed among the studied herds. Similar values have been reported by Moreira et al (2018) for herds in southern Brazil. High volumes of milk solids from Holstein cattle are delivered to milk processing plants to produce milk derivatives in southern Brazil.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Relevant FY (277.81 kg/lactation/year) and PY (255.47 kg/lactation/year) were observed among the studied herds. Similar values have been reported by Moreira et al (2018) for herds in southern Brazil. High volumes of milk solids from Holstein cattle are delivered to milk processing plants to produce milk derivatives in southern Brazil.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that FY heritability was always moderate, varying from 0.21 to 0.27, reinforcing the absence of GEI. Similar heritability estimates have been reported by Moreira et al (2018) and Paula et al (2008) for Holstein herds in Brazil and by van der Laak et al (2016) for herds in Netherlands. However, higher FY heritability has been reported elsewhere for Holstein cattle.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations